Resistencia de especies de Manihot a Mononychellus tanajoa (acariformes), Aleurotrachelus socialis y Phenacoccus herreni (hemiptera) - Burbano Melo, M.; Carabalí Muñoz, A.; Montoya Lerma, J.; Bellotti, Anthony C. (2007)
Wild species of the genus Manihot offer a valuable and potential source of resistance genes for the control of the majority of insect pests of cassava (Manihot esculenta). Recently, this characteristic has being exploited to develop strains resistant to pests and diseases through inter-specific crosses with wild Manihot species. In order to find new sources of resistance in Manihot species, two wild Brazilian species, M. flabellifolia and M. peruviana, were evaluated and compared to commercial genotypes of M. esculenta to determine potential resistance against three of the major cassava pests in the Americas, Africa and Asia: the mite Mononychellus tanajoa, the mealybug (Phenacoccus herreni) and the whitefly (Aleurotrachelus socialis). The research was carried out at CIAT, Palmira, under controlled conditions (25±5 ºC, 60±10 RH, 12L/D) using screening and bioassay methodologies assisted by controlling infestation and damage levels. The results showed that the genotypes M. flabellifolia (444-002) and M. peruviana (417-003 and 417-005) exhibited highest levels of resistance against M. tanajoa and A. socialis, while the genotypes M. flabellifolia (444-002) and M. peruviana (417-003) showed middle levels of resistance against P. herreni. The importance of these sources of resistance is discussed in light of the diversity conservation and host plant resistance programs and a component of integrated pest management.